CITRA TOKOH NY. TALIS DALAM NOVEL NY. TALIS (KISAH MENGENAI MADRAS) KARYA BUDI DARMA: KAJIAN PSIKOANALISIS - Ichlasul Yulianto, Mochammad (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2017)
The purpose of the study is to understand the idea, ego, and superego of Ny. Talis personalities which revealed in the novel of Ny. Talis (Kisah Mengenai Madras) by Budi Darma. Based on the purpose of this research, the theory which is used to analyze the data is Sigmund Freud’s psychoanalyis theory, it focuses on three personalities, namely idea, ego and superego. The results shows that complex Ny. Talis’s personalities are depicted in other words, the novel is psychologi cally Ny. Talis is described as a figure af someone who feel quilty easily and being isolated waman. Moreover Ny. Talis is well known as a person who has multiple personality. Ny Talis is stigmatized as an isolated or excluded woman in Surabaya as the setting of the novel.